Effects of parental psychological control on mobile phone addiction among college students: the mediation of loneliness and the moderation of physical activity - Jinfu Wang; Liang Li; Qinmei Wu; Na Zhang; Rulan Shangguan; Guan Yang (BMC Psychology)
Abstract Objective Prior studies have shown that parental psychological control is linked to an increased risk of mobile phone addiction. Nevertheless, few studies have analyzed the potential mechanisms that may mediate or moderate this association. This study aims to investigate the role of loneliness as a mediator in the relationship between parental psychological control and mobile phone addiction, as well as the potential moderating effect of physical activity on this mediation process. Methods A survey involving 268 Chinese college students (mean age = 20.58 years, SD = 5.23) utilized the Parental Psychological Control Questionnaire, Mobile Phone Addiction Tendency Scale, Physical Activity Level Scale, and Loneliness Scale. In terms of data analysis, descriptive analysis, Pearson correlation analysis, and moderated mediation effect tests were conducted sequentially. Results The results indicated that, after controlling for gender and age, parental psychological control positively predicted mobile phone addiction among college students (B = 0.083, p = 0.034). Loneliness played a partial mediating role in the association between parental psychological control and mobile phone addiction among college students. Additionally, physical activity moderated the impact of loneliness on mobile phone addiction in college students (B = -0.010, p = 0.035). Conclusion This study deepens our understanding of how parental psychological control leads to mobile phone addiction. Concurrently, it underscores the importance of enhancing physical activity to mitigate the adverse effects of loneliness.